Cerita Rakyat Interaktif "Malin Kundang" - Muchamad Fajri Amirul Nasrullah; Sandi Prasetyaningsih; Riki Riki; Michael Jones; Harist Setya Nugraha (JURNAL INTEGRASI, 2021)
People are increasingly encouraged by the advancement of science and technology to use and develop technical achievements in a variety of sectors, particularly multimedia. One way to make use of interactive folklore that is suitable and enjoyable, especially for youngsters, is to produce interactive folklore. Because it is packaged in two unique and fascinating studies for its users, it is intended to be something new and not dull in the process of learning and reading for youngsters. The researcher used the folklore "Malin Kundang," which is based on West Sumatra folklore, in this study. This interactive tale was created utilizing a two-dimensional animation base. Users will be provided a story of Malin Kundang and his mother, going from young Malin Kundang to married Malin Kundang, in this interactive folklore. This interactive folklore contains numerous distinct narratives, each with a different ending and story progression, so that children will be engaged and not bored by the varied storylines and may learn from the various qualities and characters in this interactive folklore